Ghosts. Season five [videorecording (DVD)] - Baynton, Mathew, 1980- (BBC Studios, 2024)
"With their guesthouse dream in ashes, Alison and Mike must find a new way to make money from their ailing estate, as a major revelation sees their plight become even more pressing. Meanwhile life (death) goes on for the Ghosts as they investigate Kitty's untimely demise, Food Club loses its appeal, Lady Button discovers hidden talents, and Robin makes a prediction that prompts the Ghosts to consider their pasts and their futures. As the bond between Alison, Mike and the Ghosts deepen, they must all decide what will come nest. Laughter, tears and surprises abound as this modern classic draws to a close"--Container insert.